1987
DOI: 10.1097/00132582-198707000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Saddle Block with Pethidine for Perineal Operations

Abstract: Small doses of morphine given intrathecally and extradurally produce long-lasting relief of chronic and postoperative pain in man (Behar et al., 1979; Wang, Nauss and Thomas, 1979). In addition to morphine, the efficacy of pethidine (Cousins et al., 1979), fentanyl (Bailey and Smith, 1980), methadone and hydromorphone (Bromage, Camporesi and Chestnut, 1980) has been studied. Using the extradural route, all the opiates, including pethidine, were able to interrupt pain at a spinal level without affecting motor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 1 publication
1
20
1
Order By: Relevance
“…A number of clinical and experimental studies (10 -22) have shown that meperidine induces spinal anesthesia and blocks action potentials, providing segmental and sensory blocks comparable in effect to lidocaine. In medicine, it has been administered intrathecally (8,10,14,16,18), spinally (13,20), and as a saddle block (11), as well as locally for intravenous regional anesthesia (21), block (15), and infiltration (22) for the effects of analgesia, anesthesia, or both.…”
mentioning
confidence: 99%
“…A number of clinical and experimental studies (10 -22) have shown that meperidine induces spinal anesthesia and blocks action potentials, providing segmental and sensory blocks comparable in effect to lidocaine. In medicine, it has been administered intrathecally (8,10,14,16,18), spinally (13,20), and as a saddle block (11), as well as locally for intravenous regional anesthesia (21), block (15), and infiltration (22) for the effects of analgesia, anesthesia, or both.…”
mentioning
confidence: 99%
“…22 Clinically, meperidine has local anesthetic activity. A number of clinical and experimental studies [24][25][26][27][28][29][30][31][32][33][34][35][36] have shown that meperidine induces spinal anesthesia and blocks action potentials, providing segmental and sensory blocks comparable to those provided by lidocaine. In medicine, it has been administered intrathecally, 22,24,28,30,32 spinally, 27,34 and as a saddle block, 25 as well as locally for intravenous regional anesthesia, 35 block, 29 and infiltration 36 for the effects of analgesia, anesthesia, or both.…”
mentioning
confidence: 99%
“…[7][8][9] Reported side effects from subarachnoid pethidine have included nausea and vomiting, pruritus, urinary retention, respiratory depression, and hypotension. 13,18 Grace and Fee observed that only subjects in the pethidine group experienced pruritus. 8 Three subjects (11.54%) from bupivacaine group developed urinary retention while none from pethidine group experienced it.…”
Section: Discussionmentioning
confidence: 99%